Experiments and modeling of by-pass pigging under low-pressure conditions. (November 2018) - Hendrix, M.H.W.; IJsseldijk, H.P.; Breugem, W.-P.; Henkes, R.A.W.M.
Highlights: Experiments for by-pass pigging under low pressure conditions have been performed. Oscillatory behaviour of the pig motion has been described by a simplified model. A controller which actively regulates the by-pass can suppress pig velocity excursions. Abstract: We present experimental and numerical results for by-pass pigging under low-pressure conditions which aided the design of a speed-controlled pig (Pipeline Inspection Gauge). Our study was carried out using air as working fluid at atmospheric pressure in a 52 mm diameter pipe of 62 m length. The experimental results have been used to validate simplified 1D models commonly used in the oil and gas industry to model transient pig behaviour. Due to the low pressure conditions oscillatory behavior is observed in the pig speed, which results in high pig velocity excursions. The oscillatory motion is described with a simplified model which is used to design a simple controller aimed at minimizing these oscillations. The controller relies on dynamically adjusting the by-pass area, which allows to release part of the excess pressure which builds up in the gas pocket upstream of the pig when the motion of the pig is arrested. Subsequently, the control algorithm is tested by a 1D transient numerical model and it was shown to successfully reduce the pig velocity excursions.